Overweight Is Associated with Seborrheic Dermatitis in Adults - Oktika Dagis, Nyai; Amani, Patwa (Sriwijaya Journal of Medicine, 2025)
Seborrheic Dermatitis (SD) is a prevalent dermatological condition marked by papulosquamous lesions, frequently found on the scalp, face, and other regions abundant in sebaceous glands. Although rarely life-threatening or communicable, SD can exert a considerable psychological influence owing to the social shame linked to inadequate hygiene, particularly among adults. This study sought to examine the correlation between body mass index (BMI) and standard deviation (SD) in the adult demographic. The study employed a cross-sectional observational methodology. Data were obtained through the examination of medical records. This study comprised 126 samples, including 44 men (66.7%) and 39 women (65.0%), aged between 26 and 45 years. Our study determined that overweight is associated with SD conditions in the adult population (p = 0.004).